2012
DOI: 10.1080/01634372.2011.633975
|View full text |Cite
|
Sign up to set email alerts
|

A Long Life With a Particular Signature: Life Course and Aging for People With Disabilities

Abstract: What does it mean to live a long life and grow old with disabilities? Or to be an aging parent and still be a caregiver to a disabled adult child? These are questions discussed in this article, the aim of which is to show how a life course perspective adds insight to the lived experience of disability and ageing of adults with disabilities. It is argued that the time concept is fundamental to the understanding of the lives of disabled people. Results are presented which challenge established knowledge regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 16 publications
3
18
1
1
Order By: Relevance
“…Some studies of those ageing with a range of impairments are emerging, and these have identified shared experiences amongst this population: ongoing life changes, related to both impairment and ageing, and a consequent need for adaptation; the effects of ageing being experienced as a ‘second disability’; and anxiety related to maintaining independence (Gilson and Netting 1997; Jeppsson Grassman et al 2012; Zarb and Oliver 1993). These experiences are evident in the literature relating to those ageing with deafblindness, as illustrated above, and may be considered features of what Putnam (2012: 92) describes as the ‘uniqueness to ageing with disability’.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies of those ageing with a range of impairments are emerging, and these have identified shared experiences amongst this population: ongoing life changes, related to both impairment and ageing, and a consequent need for adaptation; the effects of ageing being experienced as a ‘second disability’; and anxiety related to maintaining independence (Gilson and Netting 1997; Jeppsson Grassman et al 2012; Zarb and Oliver 1993). These experiences are evident in the literature relating to those ageing with deafblindness, as illustrated above, and may be considered features of what Putnam (2012: 92) describes as the ‘uniqueness to ageing with disability’.…”
Section: Discussionmentioning
confidence: 99%
“…In this process, they contested and reinvented discourses about what ageing, disability and many other issues, such as social justice and intergenerational relationships, meant to them (Minkler & Holstein, ). Together, they demonstrated how they have long managed to handle significant impairments and mastered effective coping strategies, showing that participation and autonomy are possible even for people who have extensive support needs (Jeppsson Grassman et al, ). A focus only on independent locations of ageing or disability, however, as suggested in current discourses and practices, would seem to marginalise the complex aspects of their experiences and identities.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Both social gerontology and disability studies tend to overlook the experience of ageing with disabilities (Kennedy & Minkler, ; Priestley & Rabiee, ) . Although lifelong disability is considered to affect the life course and is a central determinant of support needs and experiences in old age (Bigby, ; Jeppsson Grassman, Holme, Taghizadeh Larsson & Whitaker, ; Zarb, ), the situations, representations and needs of this group remain largely underexplored (Bigby, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings from this study illustrate the need for people to have the opportunity to make choices about their future (Walmsley, 1996), which includes having the necessary supports to be meaningfully engaged in planning and decision-making, as well as learning the skills necessary to be present and participate in the community (Buys et al , 2008). As autonomy is a dynamic process, corresponding perspectives and supports need to be reviewed frequently as access to information and/or acquired experiences shape preferences over time (Jeppsson Grassman et al , 2012).…”
Section: Resultsmentioning
confidence: 99%